2018
DOI: 10.1177/1534735418762537
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor and Immunomodulatory Activities ofGanoderma lucidumPolysaccharides in Glioma-Bearing Rats

Abstract: Malignant gliomas are the most common brain tumors with high rates of recurrence and mortality. Novel approaches are in research, and immunotherapy emerges as a promising strategy. Recently, scientific attention has been focused on Ganoderma lucidum polysaccharides (GL-PS), one of the critical bioactive components of G lucidum, which have been recognized as a promising natural source of immunomodulatory and anticancer compounds. It remains unknown whether the GL-PS have any immunomodulatory and anticancer effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 41 publications
(42 reference statements)
0
53
0
2
Order By: Relevance
“…Microbial exopolysaccharides (mEPS), composed of numerous monosaccharide units linked by glycosidic bonds in linear or branched chains, are considered as one class of these active biomacromolecules. mEPS are recognized as important biological response modifiers [1,2]. eir biological activities are greatly influenced by their characteristics such as molecular weight, charge density, monosaccharide composition, acidic fraction, types of glycosidic linkage, and substitution groups [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Microbial exopolysaccharides (mEPS), composed of numerous monosaccharide units linked by glycosidic bonds in linear or branched chains, are considered as one class of these active biomacromolecules. mEPS are recognized as important biological response modifiers [1,2]. eir biological activities are greatly influenced by their characteristics such as molecular weight, charge density, monosaccharide composition, acidic fraction, types of glycosidic linkage, and substitution groups [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…eir biological activities are greatly influenced by their characteristics such as molecular weight, charge density, monosaccharide composition, acidic fraction, types of glycosidic linkage, and substitution groups [3][4][5]. Specifically, sulfated polysaccharides have been proved to possess potent antitumor and antioxidant activities that made them gain increasing attention as potential new natural therapeutic materials and good substitutes for synthetic agents [1,4]. It has been found that mEPS produced by Bacillus amyloliquefaciens show significant therapeutic activities against gastric tumors [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The polysaccharide is the main active ingredient of Cyclocarya paliurus [14]. Polysaccharides, as natural biological macromolecules, have a variety of biological activities and are closely related to the maintenance of biological processes, for example, fungi and Ganoderma, which have inhibitory effects on tumor cells [17,18]. There are few studies on the antitumor effect of CPP.…”
Section: Discussionmentioning
confidence: 99%
“…64,66 In studies investigating G. lucidum spores and β-glucagon effects in rats, it has been reported that they inhibit inflammatory markers and tumor cells and increase survival of rats. 5,62,67,68 Different results can be obtained depending on the cell type in studies performed in cancer cells. Ruan et al conducted a study on different cancer cells have reported that HepG2 cells do not induce apoptosis, although they cause apoptosis in HeLa and Caco-2 cells.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%